Child abuse in Malaysia: an overview from Islamic perspective - Hamdzah, Hazwani; Fatah Yasin, Raudlotul Firdaus (Universiti Teknologi Malaysia, 2016)
Children are an integral asset for future development of a nation. In lieu of this notion, almost all countries pay considerable attention to their development and wellbeing. In recent times, child abuse has become a worrying phenomenon that can no longer be ignored. This issue is constantly making headlines in Malaysian national newspapers. The statistics issued by the Department of Social Welfare Malaysia indicates that the number of child abuse cases reported increased dramatically from 2008 until 2013. In 2008, 2300 children were reported to be abused, and the figure has increased to 44.1% in 2013 when 4119 children were reported to have been abused by either their own parents or guardians. In Islam, children are a monumental trust from Allah (SWT) and parents are mandated with the responsibility to raise and educate them. A well-endorsed treatment is thus a personal and religious imperative. Conversely, maltreatment and abuse are indeed a great sin. Hence, this paper seeks to discover an overview of child abuse in Malaysia and how Islam prohibits child abuse by critically analysing existing research works, articles, journals, theses and books from library and archive. An analysis of Qur’anic verses and interpretations related to prohibition of child abuse, as well as the kind treatment of Prophet Muhammad (PBUH) and his companions towards the children and the youth, is also carried out, which serves as the evidence and living examples of child abuse prevention and its implementation during this modern time in Malaysia. It is expected that this study will be able to create awareness in the society and offer theoretical solutions derived from the original source of knowledge, that is, the Divine Revelation.